Solar‐Powered Gram‐Scale Ammonia Production from Nitrate - Gnanasekar, Paulraj; Peramaiah, Karthik; Zhang, Huafan; Alsayoud, Ibrahim G.; Subbiah, Anand S.; Babics, Maxime; Ng, Tien Khee; Gan, Qiaoqiang; De Wolf, Stefaan; Huang, Kuo‐Wei; Ooi, Boon S. (Small (Weinheim an der Bergstrasse, Germany), 2024)
The photoelectrochemical (PEC) method has the potential to be an attractive route for converting and storing solar energy as chemical bonds. In this study, a maximum NH3 production yield of 1.01 g L−1 with a solar‐to‐ammonia conversion efficiency of 8.17% through the photovoltaic electrocatalytic (PV‐EC) nitrate (NO3−) reduction reaction (NO3−RR) is achieved, using silicon heterojunction solar cell technology. Additionally, the effect of tuning the operation potential of the PV‐EC system and its influence on product selectivity are systematically investigated. By using this unique external resistance tuning approach in the PV‐EC system, ammonia production through nitrate reduction performance from 96 to 360 mg L−1 is enhanced, a four‐fold increase. Furthermore, the NH3 is extracted as NH4Cl powder using acid stripping, which is essential for storing chemical energy. This work demonstrates the possibility of tuning product selectivity in PV‐EC systems, with prospects toward pilot scale on value‐added product synthesis. Nitrate pollution is a global issue, converting it to ammonia‐fertilizer via nitrate reduction with renewable energy is attractive. This study explores how voltage and external resistance affect product selectivity in NiCo‐layered double hydroxides (LDH)‐based nitrate reduction reactions, paving the way for precise control and efficient conversion.